Sepakbola: Kapasitas Vital Paru dan Tingkat Kebugaran Jasmani - Rusmanto; Lardika, Rola Angga; Gazali, Novri (Journal Sport Area, 2020)
Lung vital capacity is the status of physiological conditions associated with the ability to treat respiration together with the increasing of physical fitness, so lung vital capacity is a process involving the mechanism of the heart and blood vessels and blood which aims to provide O2 to cells in the body and transport CO2 out of body. The purpose of this study is to determine the correlation between lung vital capacity and the physical fitness level of Pendor Football Athletes from Universitas Riau. The collecting of data in this study is data from lung vital capacity tests and physical fitness with a sample of 20 athletes. Analysis of the data that used to process data is Product Moment correlation. For determining the significance of data, it uses formulation of t distribution. The results that obtained from lung vital capacity have a significant correlation with the level of physical fitness, this is indicated by the results obtained by r count (0622) > r table (α = 0.05) = 0.456. Meanwhile, t distribution test is obtained the result of t count (3,369) > t table (1,734). So H0 is refused and Ha is accepted. Thus it can be concluded that there is a significant correlation between the lung vital capacity (x) and the level of physical fitness (y).